Stability of erythrocyte sedimentation in a constant magnetic field - Kizilova, N. (My University, 1989)
The stability of erythrocyte sedimentation in the presence of a transverse component of the ponderomotive force is investigated. The processes of erythrocyte aggregation lead to the sedimentation being unstable with respect to small variations of the uniform horizontal cell distribution in the sedimentation tube. If an axisymmetric cell distribution is assumed, the system of equations describing erythrocyte sedimentation in blood plasma can be reduced to two-dimensional form and the investigation of this system, both with and without allowance for the viscous components and inertial terms, has shown that it is unstable with respect to small perturbations. The instability may sometimes result in the widely employed ESR test not being exclusively determined by the theological characteristics of the blood modified, for example, by disease. Accidental shaking of the capillary containing the blood or some other mechanical influence may lead to aggregation of the erythrocytes at the top of the tube and a sharp acceleration of the, entire sedimentation process.
Keywords: stability; sedimentation; erythrocyte